Forma Analysis of Particle Swarm Optimisation for Permutation Problems. (14th April 2008) - Gong, Tao; Tuson, Andrew L.
Abstract : Particle swarm optimisation (PSO) is an innovative and competitive optimisation technique for numerical optimisation with real-parameter representation. In this paper, we examine the working mechanism of PSO in a principled manner with forma analysis and investigate the applicability of PSO on the permutation problem domain. Particularly, our derived PSO schemes are empirically studied based on the quadratic assignment problem (QAP) benchmarks to justify its comparable performance, which in turn implies the benefits of our approach in applying PSO to the discrete problem domain.